2005
DOI: 10.1103/physrevb.72.144422
|View full text |Cite
|
Sign up to set email alerts
|

Magnetodielectric response of the spin-iceDy2Ti2O7

Abstract: We report the magnetodielectric response of single crystals of the spin-ice compound Dy 2 Ti 2 O 7 down to 0.26 K. The dielectric constant under zero magnetic field exhibits a clear decrease reflecting the development of the local two-spins-in, two-spins-out structure below about 1.2 K. Both the real and imaginary parts of the dielectric constant under magnetic fields sensitively respond to various changes in the spin structures. We found that the real part can be described in terms of local spin correlations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 14 publications
5
64
0
2
Order By: Relevance
“…We confirmed this magnetoelectricity in Dy 2 Ti 2 O 7 and, in addition, demonstrated that the dielectric dynamics gets dramatically modified close to the monopole liquid-gas transition resulting in a critical speeding-up. In order to confirm its precise link to monopoles, detailed measurements of the critical magnetic dynamics at frequencies extending 1 kHz are now called for 13 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We confirmed this magnetoelectricity in Dy 2 Ti 2 O 7 and, in addition, demonstrated that the dielectric dynamics gets dramatically modified close to the monopole liquid-gas transition resulting in a critical speeding-up. In order to confirm its precise link to monopoles, detailed measurements of the critical magnetic dynamics at frequencies extending 1 kHz are now called for 13 .…”
Section: Discussionsupporting
confidence: 68%
“…Full spectra of the dielectric response are presented in Fig. 3 for selected magnetic fields and temperatures in complete agreement with previously reported results 7 . The spectra contain a constant field-independent contribution to e 00 , which translates via the Kramers-Kronig relations to e 0 c:l: ðnÞ $ À ln n giving rise to a constant negative slope in the permittivity on a logarithmic frequency scale, see Supplementary Note 1.…”
Section: Magnetic and Dielectric Responsesupporting
confidence: 77%
See 1 more Smart Citation
“…Other important experimental results for the magnetic field behavior of Dy 2 Ti 2 O 7 and Ho 2 Ti 2 O 7 the reader can find, e.g., in [142,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159]. …”
Section: Spin Ices In An External Magnetic Fieldmentioning
confidence: 99%
“…The positive magnetodielectric responses below 55K in Figure 4b are attributable to that magnetic fields play a role of preventing low-temperature reduction in dielectric constants when nearest-neighbor spin correlation increases for antiferromagnetic structures [23].…”
Section: Resultsmentioning
confidence: 99%